Preclinical Safety Evaluation and Human Dosimetry of [18F]MK-6240, a Novel PET Tracer for Imaging Neurofibrillary Tangles. - Koole, Michel; Lohith, Talakad G.; Valentine, John L.; Bennacef, Idriss; Declercq, Ruben; Reynders, Tom; Riffel, Kerry; Celen, Sofie; Serdons, Kim; Bormans, Guy; Ferry-Martin, Sandrine; Laroque, Philippe; et al. (Molecular Imaging & Biology, 2020)
Purpose: [18F]MK-6240 is a selective, high-affinity positron emission tomography tracer for imaging neurofibrillary tangles, a key pathological signature that correlates with cognitive decline in Alzheimer disease. This report provides safety information from preclinical toxicology studies and first-in-human whole-body biodistribution and dosimetry studies of [18F]MK-6240 for its potential application in human brain imaging studies.Procedures: MK-6240 was administered intravenously (IV) in a 7-day rat toxicity study at × 50, × 100, and × 1000 dose margins relative to projected highest clinical dose of 0.333 μg/kg. The IV formulation of MK-6240 for clinical use and the formulation used in the 7-day rat toxicity study was tested for hemolysis potential in human and Wistar rat whole blood. Sequential whole-body positron emission tomography scans were performed in three healthy young subjects after IV bolus injection of 180 ± 0.3 MBq [18F]MK-6240 to characterize organ biodistribution and estimate whole-body radiation exposure (effective dose).Results: MK-6240 administered IV in a 7-day rat toxicity study did not show any test article-related changes. The no-observed-adverse-effect level in rats was ≥ 333 μg/kg/day which provides a margin 1000-fold over an anticipated maximum clinical dose of 0.333 μg/kg. Additionally, the MK-6240 formulation was not hemolytic in human or Wistar rat blood. [18F]MK-6240 activity was widely distributed to the brain and the rest of the body, with organ absorbed doses largest for the gall bladder (202 μGy/MBq). The average (±SD) effective dose was 29.4 ± 0.6 μSv/MBq, which is in the typical range for F-18 radiolabeled ligands.Conclusions: Microdoses of [18F]MK-6240 are safe for clinical positron emission tomography imaging studies. Single IV administration of 185 MBq (5 mCi) [18F]MK-6240 is anticipated to result in a total human effective dose of 5.4 mSv and thus allows multiple positron emission tomography scans of the same subject per year.